2018
DOI: 10.1097/ico.0000000000001690
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Keratitis After Ocular Surface Stem Cell Transplantation

Abstract: Despite successful OSST surgery, infectious keratitis is relatively common, and aggressive medical/surgical therapy is warranted. Prophylactic topical antibiotics and a cicatrizing conjunctivitis diagnosis may account for the high proportion of fungal keratitis in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This is comparable to an epidemiologic study of bacterial keratitis from Vancouver, Canada [ 11 ], but is much higher compared to the reports of infectious keratitis from northern California (17.7%) [ 12 ], and southern Texas (17.6%) [ 10 ]. The ocular surface disease impairs the defense mechanisms of the external eye and cornea, moreover, the decreased integrity of the corneal epithelium, persistent epithelial defects, and associated corneal inflammation can contribute to the increased risk of infectious keratitis in these patients [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable to an epidemiologic study of bacterial keratitis from Vancouver, Canada [ 11 ], but is much higher compared to the reports of infectious keratitis from northern California (17.7%) [ 12 ], and southern Texas (17.6%) [ 10 ]. The ocular surface disease impairs the defense mechanisms of the external eye and cornea, moreover, the decreased integrity of the corneal epithelium, persistent epithelial defects, and associated corneal inflammation can contribute to the increased risk of infectious keratitis in these patients [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable to an epidemiologic study of bacterial keratitis from Vancouver, Canada 12 , but is much higher compared to the reports of infectious keratitis from northern California (17.7%) 10 , and southern Texas (17.6%) 11 . The ocular surface disease impairs the defense mechanisms of the external eye and cornea, moreover, the decreased integrity of the corneal epithelium, persistent epithelial defects, and associated corneal in ammation can contribute to the increased risk of infectious keratitis in these patients 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Cheung et al reported the rate of infectious keratitis to be 18.7%. 26 Occasional epithelial shedding and breakdown, disturbances in precorneal tear film composition and stability, and altered ocular surface defense mechanisms are of probable risk factors for the development of bacterial keratitis after KLAL. These become especially important when follow-up duration is high, which increases risk of transplanted LSC failure.…”
Section: Discussionmentioning
confidence: 99%